Video in qualitative research : analysing social interaction in everyday life - Heath, Christian, 1952-; Hindmarsh, Jon.; Luff, Paul. (Los Angeles : SAGE, 2010)
Provides practical guidance for both students and academics on how to use video in qualitative research, how to address the problems and issues that arise in undertaking video-based field studies and how to subject video recordings to detailed scrutiny and analysis.
Video, analysis and the social sciences -- Access, ethics and project planning -- Collecting audio-visual data -- Analysing video : developing preliminary observations -- Matters of context : objects, participation and institutional practice -- Preparing presentations and publications -- Implications, applications and new developments -- Appendix 1. Transcription notes -- Appendix 2. Example of an introductory letter seeking access to record -- Appendix 3. Tips for data sessions -- Appendix 4. Selected references to our research studies.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social sciences -- Research -- Audio-visual aids; Qualitative research -- Audio-visual aids; Video recording; Electronic books